Tephrochronological Studies in Japan: Diverse Applications, Especially to the Geomorphology of the Kantō Plain - Kaizuka, Sōhei (ERDKUNDE, 1958)
The Japanese islands saw so many volcanic eruptions during the Quaternary and were so widely covered by volcanic ashes that here in the field of geochronology the tephrochronological method is of special importance. The present work first gives an overview of the results of tephrochronological studies in Japan with respect to various fields, such as volcanology, soil science, archaeology, stratigraphy, etc.; secondly, it describes in more detail the application of the tephrochronological method to the geomorphology of the Kantö Plain, the largest plain in Japan. In geomorphology, the tephrochronological method is used for two purposes: on the one hand, to establish correlations between surfaces (e.g. terraces), and on the other hand, to reconstruct the ancient relief. Whatever the aim, the first step of a tephrochronological study is to establish a stratigraphic classification of the ash layers, which then allows a correlation of these classified ash layers over a greater distance. For a correlation it is very informative to follow the characteristic inclusions such as pumice, cinders and soil particles and furthermore to analyze the composition of the volcanic ash with respect to the heavy minerals. Based on these tephrochronological working methods, the relief surfaces of the Kantö Plain are divided into five main stages and finally the evolution of the Kantö Plain during the Quaternary is shown.